Health inequalities in hospitalisation and mortality in patients diagnosed with heart failure in a universal healthcare coverage system. Issue 9 (13th June 2018) - Garcia, Raquel; Abellana, Rosa; Real, Jordi; del Val, José-Luis; Verdú-Rotellar, Jose Maria; Muñoz, Miguel-Angel
Abstract : Background: Information regarding the effect of social determinants of health on heart failure (HF) community-dwelling patients is scarce. We aimed to analyse the presence of socioeconomic inequalities, and their impact on hospitalisations and mortality, in patients with HF attended in a universal healthcare coverage system. Methods: A retrospective cohort study carried out in patients with HF aged >40 and attended at the 53 primary healthcare centres of the Institut Català de la Salut in Barcelona (Spain). Socioeconomic status (SES) was determined by an aggregated deprivation index (MEDEA). Cox proportional hazard models and competing-risks regression based on Fine and Gray's proportional subhazards were performed to analyse hospitalisations due to of HF and total mortality that occurred between 1 January 2009 and 31 December 2012. Results: Mean age was 78.1 years (SD 10.2) and 56% were women. Among the 8235 patients included, 19.4% died during the 4 years of follow-up and 27.1% were hospitalised due to HF. A gradient in the risk of hospitalisation was observed according to SES with the highest risk in the lowest socioeconomic group (sHR 1.46, 95% CI 1.27 to 1.68). Nevertheless, overall mortality did not differ among the socioeconomic groups. Conclusions: In spite of finding a gradient that linked socioeconomic deprivation to an increased risk of hospitalisation, there were no differences in mortality regarding SES in a universal healthcare coverage system.